Re-aerosolization in liquid-based air samplers induces bias in bacterial diversity. Issue 11 (2nd November 2019) - Lemieux, Joanie; Veillette, Marc; Mbareche, Hamza; Duchaine, Caroline
Abstract: Bioaerosols collected in a liquid-based sampler can be re-aerosolized into the airflow during collection and lost or concentrated in the collection fluid and overestimated during the subsequent analyses. Very little information is available concerning the specific impact on bioaerosol quantification and diversity and wrong evaluation of pathogens or potentially harmful microorganisms concentration could lead to incorrect data interpretation and inaccurate exposure risk assessment. The aim of this two-part study was to better understand how evaporation impacts the results obtained from liquid-based samplers. Bacterial consortium was spiked in the collection vessels of the Coriolisµ ® and the BioSampler ® and the bacterial concentration was monitored after running the samplers in vitro. Relative ratios of the bacteria were analyzed using qPCR (before/after). A field study in which liquid-based air samplers in a natural environment were compared to filter-based samplers was performed. This allowed for the relative characterization of either concentration or the re-aerosolization between the two samplers using high throughput sequencing methods. Amongst the four strains of bacteria examined in vitro, results suggest differential behavior between concentration or re-aerosolization from the liquid. Re-aerosolization of bacteria is difficult to predict as the cell-surface hydrophobicity, the liquid-based air sampler and its flowrate can influence it. The sequencing results from field samples confirmed the loss of entire genera by re-aerosolization ( Brevundimonas, Clostridium, Mycobacterium, and Smithella ) out of the BioSampler ® while concentration of several other genera were reduced (Bradyrhizobium, Delftia, Propionibacterium, and Sphingomonas ). These observations suggest that evaporation in liquid samplers might lead to over- or underestimation of the prevalence of some genera. Copyright © 2019 American Association for Aerosol Research Abstract :